Sistem Pendukung Keputusan Penentuan Siswa Berprestasi Menggunakan Weighted Product Berbasis Website di SDN Pandanwangi Jombang - Rahmawati, Shella; Lazulfa, Indana (Inovate, 2023)
One of the educational institutions at Jombang district is Pandanwangi State Elementary School which applies development of student's potential for their abilities and knowledge. Problem in the assessment process of outstanding students at Pandanwangi State Elementary School is that the school doesn’t have a grading system that can be used transparently and professionally. This study aims to design and implement the Weighted Product method in the decision support system for determining outstanding students at Pandanwangi State Elementary School based on the website. Decision support system for outstanding students was made based on a website using php programming language CodeIgniter and MySQL as a database. Method that used in this study is Weighted Product, this method was chosen because time required in the calculation is more efficient. Weighted Product method can make the assessment process for outstanding students at Pandanwangi State Elementary School more appropriate, and the results can be used as a reference in making appropriate decisions. Result of this study is a decision support system for outstanding students. With 7 criteria for the average value of the report card, the mandatory extra-curricular value of scouting, sports value, attendance, discipline, activeness and religious value obtain the best results was Alternative-20 whose the name Lintang Dwi A. Keywords: decision support system, student achievement, weighted product